Optimizing Mental Health in Islamic Boarding School Students: Balancing Physical and Mental Endurance for Effective Qur'an Memorization - Muttaqin, M Imamul; Hambali, Muh; Ismail, Adawiyah binti; Mulyadi, Mulyadi; Hady, M Samsul (JURNAL AL-TANZIM, 2024)
This research aims to analyze the approach of the Tahfidzul Qur'an Islamic boarding school in handling the mental health disorders of students. The method used is a qualitative case study type. Data collection techniques are carried out through interviews, observation and documentation. The data analysis technique consists of three lines of activity: data reduction, data presentation, and concludingand . The research results show that the process of memorizing the Al-Qur'an requires high concentration and optimal mental endurance so that students can carry out routine activities of memorizing the Al-Qur'an; they also must study in formal education. To support this, physical and spiritual endurance is needed to avoid mental health disorders. The impact of this physical and spiritual imbalance is felt in adaptation and concentration, and it not only affects individual health but also plays a vital role in preparing students to read and memorize the Koran well. The way to prevent this is to use an approach to establishing discipline and Islamic mystical therapy. Islamic boarding school caregivers provide practice to students who experience mental disorders in the form of stress, weak memorization ability, and depression through a spiritual approach.